Implementation of Some Finite Difference Methods for the Pricing of Derivatives using C++ Programming. - Ampadu, Ebenezer (Worcester Polytechnic Institute, 2007)
In this project,European Call and Put options,and also American Call and Put options have been priced by some finite difference methods using the C++ programming language.The report describes the following:The theory behind the pricing of options,some pricing methods,and how some finite difference pricing methods have been implemented in C++.